Genetically and geochronologically contrasting plagiogranites in South Central Tianshan ophiolitic mélange: Implications for the breakup of Rodinia and subduction zone processes. (1st December 2015) - Jiang, Tuo; Gao, Jun; Klemd, Reiner; Qian, Qing; Zhang, Xi; Wang, Xinshui; Tan, Zhou; Zhu, Zhixin
Highlights: Both plagiogranites have no genetic relationship with the ophiolite. The 775 Ma plagiogranite is associated with the breakup of the Rodinia. The 416 Ma plagiogranite is related to the subduction of the South Tianshan Ocean. Abstract: Plagiogranites are exposed as exotic blocks at two localities (Wuwamen and Guluogou) in the South Central Tianshan ophiolitic mélange and have U–Pb zircon ages of 775 ± 11 Ma and 416 ± 4 Ma, respectively. The Wuwamen plagiogranites have low-K tholeiitic to medium-K calc-alkaline and weakly peraluminous compositions. They further display relatively low concentrations of total rare earth elements (REEs), pronounced positive Eu anomalies and distinct depletions of P and Ti. The trace element characteristics, whole-rock initial 87 Sr/ 86 Sr ratios from 0.708812 to 0.708839 and negative ε Nd ( t ) values from −6.4 to −6.2 suggest that the granitic magma was derived from low degree partial melting of amphibolites at middle to lower crustal levels with hornblende as the dominant residual phase. In contrast, the Guluogou plagiogranites are strongly peraluminous and are characterized by an enrichment of both large ion lithophile elements (LILEs) and light rare earth elements (LREEs). Negative anomalies of Nb, Ta, P and Ti are in accordance with the geochemical signature of Andean arc-type granites. The zircon ε Hf ( t ) values from −6.1 to +2.4, the corresponding two-stage Hf model ages ( T DM C  = 1259–1798 Ma) and the ε Nd ( t ) values from −5.0 to −2.9 favor partial melting of ancient continental crust, which was contaminated by some juvenile material from a depleted-mantle wedge, for the origin of the Guluogou plagiogranites. Thus, we conclude that the Wuwamen and Guluogou plagiogranites have no direct genetic relationship with the ophiolites and occur as exotic blocks in the ophiolitic mélanges. It is further suggested that the 775 Ma Wuwamen plagiogranites originated during the breakup of Rodinia, whereas the 416 Ma Guluogou plagiogranites were generated in an Andean-type active continental margin environment related to the northward subduction of the South Tianshan Ocean.